The Association of Herbal Medicine Consumption Habits with Quality of Life Among Farmers with Chronic Diseases - suharmantoarman suharmanto (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2025)
Chronic diseases can occur due to unhealthy lifestyle changes that disrupt daily activities and decrease quality of life. This study aims to analyse the association of herbal medicine consumption habits with quality of life among farmers with chronic diseases. This study is an observational analytic study with cross-sectional approach. The study was conducted in Marga Agung Village, Jati Agung District, South Lampung in May-October 2024. The variables used were herbal medicine consumption habits and quality of life. Sampling technique using simple random sampling of 42 farmers. The sample inclusion criteria in this study include aged 25-65 years, able to read and write, and willing to be respondents. The exclusion criteria in this study include households that have a history of disease complications. The independent variables in this study is herbal medicine consumption habits and dependent variable is quality of life. Herbal medicine consumption habits was measured using a questionnaire and quality of life was measured using the WHOQOL-BREF questionnaire, which has 4 domains consisting of physical health, psychological health, social relationships, and family environment. The collected data was then edited, coded, processed, and cleaned. Data analysis using the Chi-Square test. There is a association between the herbal medicine consumption habit and quality of life in the psychological and environmental domains, but it is not related to the physical and social dimensions.